Rancang Bangun Sistem Informasi Penjualan Sparepart dan Jasa Servis Motor - Delviani Kurniawati Djami; Ferdinandus Lidang Witi; Anastasia Mude (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
Benneta Motor Workshop is one of the individual businesses that was founded in 2017, engaged in the business of selling motorcycle spare parts and servicing services. In running its business, Benneta workshop still uses conventional systems so that there are several obstacles found starting from the data management process, purchase transactions, sales and service services, to the process of making reports which are still recorded manually in notes and stored in a ledger so that it is still less efficient. in terms of time and process. Conventional systems cause the data to be inaccurate and not fast in recording so it takes a long time to do it. The purpose of this research is to build an information system for selling spare parts and motorcycle service using Visual Basic.Net programming language and MySQL database. In this study, the authors used a qualitative descriptive research method. The design method used in this application uses the waterfall method and the testing method used by the author is blackbox testing. With the creation of this system, it is hoped that it will provide efficiency and work effectiveness at the Benneta Motor Workshop.